Measures and measurement: Process and practise - Batt, Peter (Elsevier Inc., 2012)
Even although case studies remain one of the most widely utilised approaches in the study of industrial markets, debate continues about the apparent lack of any consistency in the way the case study method is applied. While acknowledging the shortcomings, this paper highlights the strengths and celebrates the diversity of the case study approach in developing and testing theory. Seven outstanding cases, selected from the Fourth Meeting of the IMP Group in Asia are presented.